Problem Solving in Labor Negotiations: Retest of a Model - Peterson, Richard; Tracy, Lane; Cabelly, Alan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
Two tests of a model of problem-solving in labor negotiations are reported, using samples of private-sector negotiations and in the Pacific Northwest.